Influence of regional features on hotel industries of Kashkadarya - Berdiyev Zhasur Kuldoshevich,; Djurakulova Ruxshona Djaxongirovna, (THE INNOVATION ECONOMY, 2026)
The article analyzes key regional features, including geographic location, climate conditions, cultural herit age and economic factors. The ways of adaptation of hotels to local conditions are considered, including architectural solutions, service innovations and marketing strategies. The main attention is paid to how hotel businesses can use these features to increase their competitiveness and improve efficiency indicators